Use of a Wearable Activity Device in Rural Older Obese Adults: A Pilot Study - Batsis, John A. (Gerontol Geriatr Med, 2016)
Objective: Assess the feasibility and acceptability of Fitbit for supporting behavioral change in rural, older adults with obesity. Method: Eight adults aged ≥65 with a body mass index (BMI) ≥30kg/m(2) were recruited from a rural practice and provided a Fitbit Zip device for 30 days. Participants completed validated questionnaires/interviews. Results: Mean age was 73.4 ± 4.0 years (50% female) with a mean BMI of 34.5 ± 4.5kg/m(2). We observed reductions in exercise confidence (sticking to it: 34.5 ± 3.3 to 30.9 ± 4.3, p = .04; making time: 18.9 ± 1.3 to 17.0 ± 2.6, p = .03) but no changes in patient activation (45.4 ± 4.3 vs. 45.0 ± 3.9). All reported high satisfaction, seven (87.5%) found Fitbit easy to use, and five (62.5%) found the feedback useful. The majority (n = 6 [75.0%]) were mostly/very satisfied with the intervention. Consistent themes emerged regarding the benefit of self-monitoring and participant motivation. Common concerns included finding time to exercise and lack of a peer group. Conclusion: Use of Fitbit is feasible/acceptable for use among older rural obese adults but may lead to reduced confidence.